CLASSIFICATION OF THE DENIAL CATEGORY IN GERMAN AND UZBEK LINGUISTICS (Academicia Globe: Inderscience Research, 2023)
The purpose of this article is to collect all the negative words in the German and Uzbek languages, to study their methods of formation, use, general and different aspects of meaning. The grammatical classification of expressions of negation in the compared languages, the views of German and Uzbek linguists on the formation of negation are studied. The article uses methods of analysis, synthesis, comparison, description and generalization. As a result of the study, the common and different features of grammatical adverbs and means that form negative sentences in the German and Uzbek languages.